ANALISIS PENGARUH LOCUS OF CONTROL, EMPLOYEE ENGAGEMENT DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT TASPEN KANTOR CABANG UTAMA SEMARANG - Kumaladewi, Ajeng Putri; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2016)
This study was conducted to determine the effect of variable locus of control, employee engagement and job satisfaction on employee performance. Distributing questionnaires made to employees of PT TASPEN KCU Semarang by respondents as many as 53 employees. The analytical method used are classical assumption test consist of normality test, multicollinierity test, heteroscedasticity test, and multiple regression analysis and hypothesis testing consist of t test and F test with a significance level of 5%. The result of the research simultaneously using F test, showed that the variables locus of control, employee engagement, job satisfaction variables influence significantly toward employee performance. Partially using t test, showed that locis of control and employee engagement had no significant effect on the results of employee performance. Job satisfaction has significant results on the performance of employees. The coefficient of determination (R square) is 0.147 which means variables locus of control, employee engagement and satisfaction performance by 14.7% effect on the performance of employees, while the remaining 85.3% is explained by other variables not included in the research model.